Роль навчальної дисциплiни «Рослинництво» у формуваннi професiйних компетенцiй майбутнього фахiвця аграрної сфери - Білоусова, Зоя Володимирівна; Белоусова, Зоя Владимировна; Bilousova, Zoia; Кенєва, Вікторія Анатоліївна; Кенева, Виктория Анатольевна; Kenieva, Viktoriia (My University, 2019)
UK: В системі реформування вищої аграрної освіти в Україні, одним із новітніх кроків на шляху наближення до європейського та світового рівнів є впровадження компетентного підходу у процес професійної підготовки, кінцевим результатом якого є набуття студентами професійних компетенцій. В статті наведені фактори, що впливають на формування профеciйних компетенцій майбутнього фахiвця аграрної сфери. EN: In the system of reforming higher agricultural education in Ukraine, one of the newest steps towards getting closer to European and world levels is the introduction of a competence-based approach into the vocational training process, the end result of which is the acquisition of professional competencies by students. The article describes the factors influencing the formation of professional configurations of the future specialist of the agricultural sector.
The role of the discipline "Plantgrower" in the formation of professional equipment of the future specialist of the agrarian sector
Keywords: професійні компетенції; аграрна сфера; якість підготовки фахівців; рослинництво; professional competences; agrarian sphere; quality of specialists training; plant growing